New transport architecture - Jones, Will. (London, United Kingdom : Octopus Publishing Group Ltd., 2006)
Jones, a freelance writer specializing in architecture and design, offers a global overview of innovative responses to contemporary transport-hub design and construction with these profiles of 36 of the world's most significant new transport structures. Organized around the four transport types (air, road, water, and rail), the projects profiled include the International Terminal at Philadelphia Airport, the Whale Jaw bus station in the Netherlands, the Yokohama International Port Terminal in Japan, and the Leuven Train Station in Belgium. Unbuilt projects are also featured, including the Beijing Airport in China. Supplementing the projects are essays by influential architects on a variety of themes pertinent to the modern transport hub, such as the importance of ecologically friendly design. The book is highly illustrated throughout with color photographs, technical drawings, and computer renderings. It will be of interest to architects, designers, and engineers.
Foreword by Ivan Harbour of Richard Rogers Partnership -- Introduction -- Adding Retail Value to Airports by David Holm -- 1. Air: Barajas Airport -- Beijing Capital International Airport -- International Terminal, Philadelphia Airport -- Virgin Atlantic Upper Class Lounge -- Bangkok International Airport -- Tianjin Binhai International Airport -- Ben Gurion International Airport -- The Politics of Public Transport by Yoichi Shimatsu & Stephen S Y Lau -- 2. Road: Vauxhall Cross Interchange -- Carpark Burda Media Park -- The Whale Jaw -- Cycle Parking Garage -- Border Station -- Sound Barrier and Cockpit -- Central Bus Station -- Underground Parking Garage -- Molndal Commuter Station -- Box Hill Transport Interchange -- Cycle Station -- Engineering in Transport Architecture by Richard Prust -- 3. Water: Yokohama International Port Terminal -- Naviduct Lock Complex -- DFDS Terminal -- Maritime Terminal -- Leith Ferry Terminal -- Ferry Landing Stage -- Falkirk Wheel -- St George Ferry Terminal -- Whitehall Ferry Terminal -- Water-based Transport Architecture by Kenneth Drucker & Eve Michel -- 4. Rail: Three Kinds of Flow -- Moscow City Transport Terminal -- King's Cross Station -- Leuven Train Station -- Stuttgart Central Station -- Worb Station -- Central Station -- Fulton Street Transit Center -- Stratford International Station -- Environmental Rail Building Design by Oliver Lowenstein -- Contact Details -- Bibliography -- Index -- Acknowledgments.
Includes bibliographical references and index.
Keywords: TERMINALS (TRANSPORTATION)